Bimbingan Kelompok Teknik Problem Solving untuk Meningkatkan Self-Efficacy Siswa dalam Perencanaan Studi Lanjut - Defina Palupi Kurniasari; Denok Setiawati (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to examine the effectiveness of group guidance services using problem-solving techniques in improving self-efficacy in planning further studies among junior high school students with low self-efficacy. The background of this study is based on the low level of self-confidence among students in planning further studies, while previous studies have focused more on improving academic self-efficacy in general and have not specifically examined further study planning through group guidance services using problem-solving techniques. This study used a quantitative approach with a one-group pretest–posttest design. The research subjects consisted of eight ninth-grade students selected using purposive sampling. The research instrument was a questionnaire on self-efficacy in planning further studies, which had been tested for validity and reliability. Data analysis was performed using the Shapiro–Wilk normality test and the paired sample t-test. The results showed a significant increase in students' self-efficacy scores from a pretest average of 72.50 to 101.00 on the posttest (p < 0.001). However, this study has limitations in terms of the relatively small sample size and the use of a research design without a comparison group, so the results need to be interpreted carefully and can be further developed in subsequent studies.